استخلاص الزيوت الاساسية من نبات الرشاد البري(Lepidium aucheri boiss) و دراسة فعاليتها الحيوية - حسام محمد كريدي; مريم ماجد كاظم (University of Thi-Qar Journal of Science, 2019)
The present study amide to extracts the essential oils from Lepidium aucheri  boiss ,where  it  was   collected  in   March  2015 from   the   northern  of   Nasiriyah  city  and  it   was  classified . it  was extracted  from  plants  by  Clevenger's  Apparatus  to  be  finally  getting around 26.45g of essential oil of 24Kg plant .Then study the bioactivity of this essential oils ,the extracted essential oils from the plant didn’t showed any toxicity toward the red blood cells. The antibacterial properties was used  five types of bacteria, Cram positive strain (Staphylococcus aureus, Streptococcus pyogenes and Enterobacter sp.) and Cram negative strain (Escherichia coli, Pseudomonas aeruginosa),These moleules showed antimicrobial activites against gram negative and gram positive bacterial . The activity of the concentration 100% showed the highest percentage inhibition there are (20mm) towards bacteria Staphylococcus and E.coli bacteria showed less inhibition ratio there are (7mm) at the same concentration .In the test of antifungal properties used four types of fungus which Asperggillus niger and Asperggillus terrus and Asperggillus flavus and Candida albicans .The results showed the highest inhibition of the fungus at concentration 100% towards A.niger where the scale inhibition is 12 mm, while the other fungi have shown high resistance toward all the prepared concentration ,especially C.albicans.        تشير الدراسة الحالية الى استخلاص الزيوت الاساسية من نبات الرشاد البري (lepidium aucheri boiss) ، اذ تم جمع النبات في اذار 2015 من شمال مدينة الناصرية ثم تم تصنيفه و استخلصت الزيوت الاساسية من النبات بواسطة جهاز كلافينجر (Clevenger's Apparatus) ، ليتم الحصـول في النهاية على ما يقارب 26.45 g من الزيوت الاساسية من 24 Kg من النبات ، ثم تم دراسة الفعالية الحيوية لها . لم تظهر الزيوت الاساسية المستخلصة من النبات اي سمية تجاه كريات الدم الحمراء ، اذ تم دراسة الخصائص المضادة للبكتيريا باستخدام خمسة انواع من البكتيريا ، و هي البكتيريا الموجبة لصبغة كرام Staphylococcus aureus , Streptococcus pyogenes and Enterobacter sp. ) ، و البكتيريا السالبة لصبغة كرام (Escherichia coli and Pseudomonas aeruginosa) ، للتحقق من فعالية الزيوت الاساسية المستخلصة ، حيث اظهرت النتائج بان لها فعالية مضادة للبكتيريا متفاوتة مقارنة بالمضاد البكتيري السبرودار(Ciprodar) . حيث عند التركيز 100%  اظهرت البكتريا Staphylococcus aureus اعلى نسبة تثبيط ، حيث كان قطر منطقة التثبيط هو (20 mm) واظهرت البكتيريا E.coli اقل نسـبة تثبيط حيث كان قطر منطقة التثبيط هو (7 mm) عند نفس التركيز . اما الخصائص المضادة للفطريات تم دراستها على اربع انواع من الفطريات وهي (Asperggillus niger و Asperggillus terrus  و Asperggillus flavus و Candida albicans) . النتائج اظهرت اعلى فعالية عند التركيز 100 % للفطر A.niger ، حيث كان قطر منطقة التثبيط هو (mm (12 ، اما الفطريات الاخرى فقد ابدت مقاومة عالية خاصة C.albicans التي لم تتأثر بجميع التراكيز المحضرة.